(untitled) - FAO (Rome, 1997)
This training manual has been prepared as a basic reference resource for national trainers, to help them structure and conduct their own courses on management at the institute level. This manual is based on the four structutral functions of management: planning, organizing, monitoring and controlling, and evaluating, each of which covered in individual modules. Within each module, the manual addresses perasive management function, including motivating, leading, directing, priority setting, communicating and delegating, which are at all times a concern to all managers. Topic such as leadership, motivation, human resources management, policies and procedures are treated separately in individual sessions.
Keywords: agricultural management